Influence Of External Examination On The Teaching And Learning Of Mathematics At The Secondary Education In Pakistan (Journal of Education and Educational Development, 2022)
This study explores the influence of external examination on teaching and learning of Mathematics at the secondary schools affiliated with provincial and private examination boards in Pakistan. By employing the explanatory sequential mixed-method approach, this study was conducted in two phases. In the first phase, the Mathematics examination papers of last five years from both provincial and private examination boards were reviewed and analyzed to understand (1) the cognitive complexities required from the learners to solve the questions, (2) the frequency and variety in which the questions were repeated and (3) the chapters of prescribed books from which the questions are selected in the examination of last five years. In the second phase, semi-structured interviews with teachers and students were conducted, along with participatory observation to understand how the examination patterns shape their teaching and learning. The findings revealed that the external examination directly influences teachers’ teaching, and indirectly students’ learning. Both the positive and negative effects of the external examination were found on the teaching and learning strategies of teachers and students, respectively.